2022
DOI: 10.1007/s10339-022-01078-1
|View full text |Cite
|
Sign up to set email alerts
|

Attention modulates incidental memory encoding of human movements

Abstract: Attention has been shown to enhance the processing of task-relevant information while suppressing the processing of task-irrelevant information. However, it is less clear whether this attentional modulation exists when there is an intrinsic dependence between task-relevant and task-irrelevant information, such as the dependence of temporal processing on spatial information. In this study, we used complex whole-body movement sequences to investigate the extent to which the task-irrelevant spatial information (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The behavioral response in the OTTER task is ecologically valid because it takes advantage of the natural behavioral tendencies of rodents. The OTTER task is also ecologically valid in relation to human incidental memory: recall in incidental memory tasks was reported to be 35%-90%, depending on the task [ 45 47 ]. We demonstrated that rats could utilize the knowledge acquired from a single experience and use it to their advantage in a different context: rats demonstrated the same behavior that resulted in the termination of the unpleasant stimulus they experienced 24 hours earlier.…”
Section: Discussionmentioning
confidence: 99%
“…The behavioral response in the OTTER task is ecologically valid because it takes advantage of the natural behavioral tendencies of rodents. The OTTER task is also ecologically valid in relation to human incidental memory: recall in incidental memory tasks was reported to be 35%-90%, depending on the task [ 45 47 ]. We demonstrated that rats could utilize the knowledge acquired from a single experience and use it to their advantage in a different context: rats demonstrated the same behavior that resulted in the termination of the unpleasant stimulus they experienced 24 hours earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four whole-body movement sequences (half performed by a female dancer and the other half performed by a male dancer, both in fitted black clothing), selected from the stimulus set of Chiou ( 2022a ), were used in the current study. No participants had viewed the movement sequences before.…”
Section: Methodsmentioning
confidence: 99%
“…1 1 Illustration of a whole-body movement sequence. Reprinted from Chiou ( 2022a ) (CC BY 4.0). Three sample video clips (A_2132, A_3212, B_3212) that illustrate movement sequences with different trajectories (A, B) and/or rhythms (2132, 3212) were published with the article Chiou ( 2022a ) and can be seen online: 10.1007/s10339-022-01078-1 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations